Report of a successful experience in Porto-PT: Educational Robotics (Research, Society and Development, 2022)
In this article, we report a successful experience in the training of high school, technical and technological teachers from the public network of Maranhão for the use of Educational Robotics in Basic Education from the completion of the training course in Robotics at the Instituto Politécnico do Porto-Instituto Superior of Engineering of Porto/Portugal. In a qualitative, reflective approach and with the characteristic of the ethnomethodology approach, we sought to characterize the context when the opportunity for continuing education in Europe for these Brazilian teachers arose, drawing a parallel between the countries Portugal and Brazil at the pandemic moment when the exchange took place. of the selected teachers, while at the same time trying to portray the praxis of Portuguese teachers, who aligned theory and practice through the interdisciplinarity process in an attractive way, arousing the scientific curiosity of different empirical knowledge of the participants. Therefore, this article highlights the relevance of continuing education in Robotics and international exchange for teachers working in Brazilian public schools.